Planejamento sistemático de layout (SLP): estudo de caso para uma agroindústria no município de Abaetetuba-PA - SOUSA, Michelli Silva (2021)
This paper aims to carry out the study of Systematic Layout Planning - PSL, for an Agroindustry, in the Municipality of Abaetetuba / PA, which is divided into three stages: Bibliographic Research for theoretical basis and support in the application of methodologies; on-site Technical Visits to collect data and information pertinent to the theme and application of the PSL stages and the preparation of the agro-industry floor plan and subsequent analysis of the Production Layouts. As a result of this study, we present the two best detailed Layouts proposals to assist management in the process of implementing agro-industry, as well as the floor plans, the map flowcharts, the multi-process chart, the process diagram, the Layout by processes defined as ideal for the production scenario, the SWOT analysis, the action plan and the strategic planning as support for the agroindustry execution.